DESIGN CLINIC EKSPLORASI MOTIF SINTANG, DESA ENSAID PANJANG KALIMANTAN BARAT - Muhammad Imam Tobroni; Rujiyanto Rujiyanto; Nick Soedarso (Jurnal Dimensi Seni Rupa dan Desain, 2018)
AbstractSintang is a one of district, which is located in the province of West Kalimantan. The population is multiethnic and the majority is Dayak and Malay. Ikat woven fabric is one of the famous art works from Sintang. It is a one of Dayak ethnic heritage that has high artistic value in manual process work with certain rituals. Workshop program called “Design Clinic” had aims to assisting in a craftsman Ikat woven fabric to create ideas that based on residence and nature Sintang environment, and also apply the ideas to bemotif or pattern, which able to be applied to other applied products. Keywords: workshop, ikat woven, motif, SintangAbstrakSintang adalah salah satu kabupaten yang berada di Provinsi Kalimantan Barat. Penduduknya multietnis, mayoritas Suku Dayak dan Melayu. Salah satu yangcukup terkenal dari Sintang ini adalah kain tenun ikatnya. Salah satu warisan budaya suku Dayak yang mempunyai nilai seni tinggi yang proses  pengerjaanya secara manual dan melakukan melalui ritual-ritual tertentu. Program pelatihan “Design Clinic”ditujukan untuk membantu pengrajin kain tenun ikat Sintang agar dapat menggali ide dari lingkungan tempat tinggal maupun alam Sintangserta menuangkan ide-ide menjadi motif yang dapat diterpakan pada produkterapan lainnya.